DEVELOPING STUDENTS' RELIGIOUS ATTITUDES THROUGH THE COBA3CC MODEL IN STATE HIGH SCHOOLS - Masbur, Masbur; Syahril, Syahril; Muzakir, Muzakir (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2023)
The COBa3CC model is a model that is the result of a collaboration based on 3 (three) circle components. That is; class-based spiritual pedagogical approach; school culture-based spiritual pedagogic approach; and a community-based spiritual pedagogic approach. The three components are mutually binding to each other. This study looked at the development of students’ religious attitudes in high school education through the COBa3CC Model. This research is qualitative, using data collection methods through observation or direct observation. In addition, to add more accurate data, the researcher used interviews with several teachers who had been previously appointed as resource persons. The results of the study show that the COBa3CC model in fostering students' religiosity has the scope of all aspects of learning. This model builds a school culture that is able to shape student character with the help of school social institutions so that values are formed and instilled in students. The implementation process will run optimally and get results or expectations if all education stakeholders in schools are involved together. The main thing is the involvement of the student's family component; the community and the environment around the school are an integral part of efforts to implement fostering students' religiosity. If the three components above work together and contribute to implementing religious values properly and simultaneously, a strong and dignified national character will be formed accompanied by the practice of religious values, not only limited to students, but will also contribute to educational institutions and the society.